HUBUNGAN PEKEBUN DAN TAUKE KELAPA SAWIT POLA SWADAYA DI DESA PANTAI CERMIN KECAMATAN TAPUNG KABUPATEN KAMPAR - Sujantara, Defri Aire; Restuhadi, I Fajar; Andriani, Yulia (Universitas Jambi, 2024)
Independent palm oil smallholders cannot market fresh fruit bunches (FFB) directly to the mill. Various factors influence the marketing process of FFB. Tauke (middlemen or collectors) play a significant institutional role in the marketing of FFB for many independent smallholders. This study aims to (1) identify the characteristics of independent palm oil smallholders, (2) analyse smallholders’ satisfaction with taukeperformance and the importance of tauke attributes from the smallholders’ perspective, and (3) examine the relationship between smallholder characteristics and their satisfaction with tauke attributes. A survey method was employed, and respondents were selected using purposive sampling, with a total sample of 88 smallholders. The findings revealthat the smallholders are predominantly of productive age, mostly senior high school graduates or equivalent, have 14–19 years of farming experience, manage land areas between 2.91 and 3.80 hectares, have 1–2 family dependents, exhibit a moderate to high level of cosmopolitanism, receive limited agricultural extension services, and access a relatively wide range of information sources. The level of satisfaction among smallholders is categorised as satisfied, and the attributes that need to be maintained are located in quadrant II of the importance-performance analysis. The relationships between smallholder characteristics and tauke performance are generally positive and significant, though with low correlation coefficients. An exception is found in the relationship between farming experience and the attribute of high pricing, which is negative and significant, albeit with a low correlation. Furthermore, smallholder characteristics are found to have a highly significant but weakly correlated positive relationship with the perceived importance of tauke attributes.Policymakers can better understand the consequences of research when it comes to bolstering agricultural supply chains. Without discounting the function of tauke or collecting dealers, the establishment of cooperative structures increases small farmers' negotiating power.